Plasma catalysis of chemical reactions - Chernyak, V.Ya.; Nedybaliuk, O.A.; Martysh, E.V.; Iukhymenko, V.V.; Prysiazhnevych, I.V.; Solomenko, Ol.V.; Veremii, Iu.P. (Вопросы атомной науки и техники, 2014)
The features of the ethanol reforming with the influence of exothermic chemical reactions on the level of non-equilibrium gas-discharge plasma are discussed. It is shown that effect of chemical reactions on the level of non-isothermality plasma itself can be extremely high and aimed at reducing the difference between translational and vibrational temperatures of plasma. The coefficient of transformation of electric energy into the chemical energy of the produced syngas has substantial increase when plasma activation of the fuel mixture of both components is transited to the activation of the oxidizer only in the hybrid plasma-catalysis partially-oxidation reformer system. Рассмотрены особенности реформирования этанола с учетом влияния экзотермических химических реакций на уровень неравновесности газоразрядной плазмы. Показано, что влияние экзотермических химических реакций на уровень неизотермичности плазмы может быть чрезвычайно высоким и направленным на снижение отрыва поступательной температуры от колебательной температуры плазмы. Переход от активации плазмой обеих компонент топливной смеси к активации только окислителя в гибридных плазмокатализных системах частично-окислительного реформинга приводит к существенному возрастанию коэффициента трансформации электрической энергии в химическую энергию полученного синтез-газа. Розглянуто особливості реформування етанолу з урахуванням впливу екзотермічних хімічних реакцій на рівень нерiвноважності газорозрядної плазми. Показано, що вплив екзотермічних хімічних реакцій на рівень неізотермічності плазми може бути надзвичайно високим і спрямованим на зниження відриву поступальної температури від коливальної температури плазми. Перехід від активації плазмою обох компонент паливної суміші до активації тільки окислювача в гібридних плазмокаталізних системах частково-окисного реформінгу призводить до істотного зростання коефіцієнта трансформації електричної енергії в хімічну енергію отриманого синтез-газу.